Influence of transmission channels of financial policies on Vietnam’s private economic development - Le, Trung Dao; Pham, Minh Tien (Journal of Finance - Marketing Research, 2023)
So far, studies have mainly looked at individual channels or groups of transmission channels of financial policy to the private sector. This study aims to analyze the impact of transmission channels of financial policy on private economic development. In addition, the study also focuses on macro-regulatory factors affecting private economic development. Research uses the balance panel data with 411 observations, collected from 2015-2021 of 63 provinces and cities of Vietnam. POOL, FEM, REM, and FGLS regression methods are used to validate the research model. Research results show that public expenditure, tax, real interest rate, and credit have an impact on Vietnam’s private economic development measured through the contribution of the private sector to the national GDP. Therefore, perfecting the transmission channels of financial policies is necessary to contribute to promoting private economic development.